Vocabulary acquisition in Moroccan- and Turkish-heritage children: A comparative study. (February 2018) - Vanbuel, Marieke; Boderé, Anneleen; Torfs, Karen; Jaspaert, Koen
Aims and objectives: In the present study, we investigated whether Moroccan- and Turkish-heritage children living in Flanders, the Dutch-speaking part of Belgium, acquire new Dutch vocabulary to the same extent when they are provided with exactly the same type of language input. Turkish-heritage children seem to have significantly lower language proficiency in Dutch, compared to their Moroccan-heritage peers. Previous studies have shown that existing language skills in the second language can affect sequential bilingual children's vocabulary acquisition in the second language considerably. Design/methodology/approach: The novel word learning of Moroccan- and Turkish-heritage six-year-olds ( N = 52) was investigated by means of four dynamic storytelling sessions in which six new object labels and six new action words were incorporated. Data and analysis: The children's conceptual and linguistic knowledge of the novel words was extensively tested. Six analyses of covariance were conducted, with origin as a between-subjects factor and proficiency in Dutch as a covariate. Findings/conclusions: Our findings indicate that Turkish- and Moroccan-heritage children acquired the novel words to almost the same extent when their prior language proficiency in Dutch was taken into account. However, Moroccan-heritage children still outperformed their Turkish-heritage peers, producing the novel object labels. Originality: For this study, we used a methodology specifically developed for this age group. In addition, we statistically controlled for the children's initial proficiency in Dutch, in order to get a better insight in the actual learning processes of new Dutch vocabulary of Moroccan- and Turkish-heritage children. Significance/implications: Our outcome suggests that initial language proficiency in Dutch is an important predictor of novel vocabulary learning. Furthermore, we argue that linguistic properties of the children's first language may play a role in second language acquisition, suggesting that a different approach to the stimulation of second language (vocabulary) acquisition in minority children of different ethnic origin may be necessary.